Volterra-type operator on the subclasses of univalent functions - Mahboobi, M. (Ukrains’kyi Matematychnyi Zhurnal, 2022)
UDC 517.5In this article, we examine the necessary and sufficient conditions for a member to belong to the class of starlike and convex functions of complex order $b$ $(b eq 0)$ and spirallike functions of type $ λ$ $\Big( {-\dfrac{π}{2}}